2011
DOI: 10.1615/jenvironpatholtoxicoloncol.v30.i3.40
|View full text |Cite
|
Sign up to set email alerts
|

Concentrations of Arsenic, Chromium, and Nickel in Toenail Samples From Appalachian Kentucky Residents

Abstract: Lung cancer rates in Appalachian Kentucky are almost twice national rates; colorectal cancer rates are also elevated. Although smoking prevalence is high, it does not explain all excess risk. The area is characterized by poverty, low educational attainment, and unemployment. Coal production is a major industry. Pyrite contaminants of coal contain established human carcinogens, arsenic (As), chromium (Cr), and nickel (Ni). We compared biological exposure to As, Cr, and Ni for adults living in Appalachian Kentuc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
26
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(29 citation statements)
references
References 32 publications
1
26
0
1
Order By: Relevance
“…Studies done in rural areas of Appalachia showed some of the highest cervical cancer rates in America where a vast majority of study participants were non-Hispanic Whites 33 In the Appalachian region, poverty rates remain high, tobacco smoking and obesity are prevalent, and many jobs in the area, like coal mining, put individuals at higher cancer risk due to carcinogens in the environment. 34,35 Heath insurance is also a factor affecting health outcomes of cancer patients. In 2008, approximately 40% of Hispanics, 26% of Blacks, and 16% of White adults did not have health insurance.…”
Section: Cancermentioning
confidence: 99%
See 1 more Smart Citation
“…Studies done in rural areas of Appalachia showed some of the highest cervical cancer rates in America where a vast majority of study participants were non-Hispanic Whites 33 In the Appalachian region, poverty rates remain high, tobacco smoking and obesity are prevalent, and many jobs in the area, like coal mining, put individuals at higher cancer risk due to carcinogens in the environment. 34,35 Heath insurance is also a factor affecting health outcomes of cancer patients. In 2008, approximately 40% of Hispanics, 26% of Blacks, and 16% of White adults did not have health insurance.…”
Section: Cancermentioning
confidence: 99%
“…In 2008, approximately 40% of Hispanics, 26% of Blacks, and 16% of White adults did not have health insurance. 36 Although the Affordable Care Act has helped millions more get access to care, a large number of uninsured patients still exist in the United States.…”
Section: Cancermentioning
confidence: 99%
“…(2931) Such studies have measured toenail metal concentrations of methylmercury, (32, 33) Pb, (34, 35) Cd, (36, 37) As, (38–40) Mn, (24, 41) Ni (20) and more. Mn and Ni have been isolated in toenail samples from welders.…”
Section: Introductionmentioning
confidence: 99%
“…Both hair and nails have been used in environmental monitoring of human exposure to arsenic and other toxic elements. [28][29][30][31][32][33][34] Compared to hair, fingernails and, in particular, toenails have slower growth rates, which makes them convenient as a biomarker of long-term exposure. [35] A large number of papers are devoted to validation of arsenic concentration in nail clippings as a tool to assess chronic effects of exposure to arsenic in drinking water.…”
Section: Introductionmentioning
confidence: 99%